GENETIC DIVERSITY, HERITABILITY AND GENETIC ADVANCE IN OKRA [Abelmoschus esculentus (L.) Moench] (Bangladesh Journal of Plant Breeding and Genetics, 2015)
Ten okra genotypes were evaluated at the Teaching and Research Farm, University of Maiduguri, Nigeria, during 2015 and 2016 dry seasons. The objective was to assess the degree of genetic diversity and heritability of different traits of okra. The combined analysis of variance revealed highly significant (p